Detection of cis- and trans-acting Factors in DNA Structure-Induced Genetic Instability Using In silico and Cellular Approaches - Wang, Guliang; Zhao, Junhua; Vasquez, Karen M. (Frontiers in Genetics, 2016)
Sequences that can adopt alternative DNA structures (i.e. non-B DNA) are very abundant in mammalian genomes, and recent studies have revealed many important biological functions of non-B DNA structures in chromatin remodeling, DNA replication, transcription, and genetic instability. Here, we provide results from an in-silico web-based search engine coupled with cell-based experiments to characterize the roles of non-B DNA conformations in genetic instability in eukaryotes. The purpose of this article is to illustrate strategies that can be used to identify and interrogate the biological roles of non-B DNA structures, particularly on genetic instability. We have included unpublished data using a short H-DNA-forming sequence from the human c-MYC promoter region as an example, and identified two different mechanisms of H-DNA-induced genetic instability in yeast and mammalian cells: a DNA replication-related model of mutagenesis; and a replication-independent cleavage model. Further, we identified candidate proteins involved in H-DNA-induced genetic instability by using a yeast genetic screen. A combination of in silico and cellular methods, as described here, should provide further insight into the contributions of non-B DNA structures in biological functions, genetic evolution, and disease development.